Are combination vaccines against influenza and COVID-19 possible? - Sanaria Fathulla (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Respiratory viral infections have been a significant clinical burden on public health, particularly for elderly patients and those with underlying health conditions. The COVID-19 pandemic brought the importance of vaccinations against viral infections to the forefront of research and most recently the need for combination vaccines against respiratory viruses such as COVID-19 and influenza has been the subject of research. Whilst efficient, combination vaccine therapy does not come without its challenges. Examples such as vaccine hesitancy, especially during recent years have become a main challenge as articles and research have become easy for the population to access, accurate or not. Whilst combination factors are also useful, the range of serotypes and mutations make it costly and difficult to stay on top of. It is clear, however, that with the correct resources and finance, a combination vaccine may become a standard in the future considering how fast the medical field of research is progressing. Moderna and several other biotechnological companies have already delved further into the development of COVID-19 and influenza vaccines, and only seem to be progressing.